A Safe and Economical Design of Composite Profile Steel Decking Systems under Fire Conditions - Nguyen, Tuan-Trung (2016)
Due to two fire incidents viz. the Basingstoke and the Broadgate Fires, composite slabs consisting of steel beams and lightly reinforced concrete slabs with steel decking showed an inherent load-carrying capacity in fire by mobilizing tensile membrane action at large displacements. Based on a number of research works on tensile membrane action of composite floor slabs, a design guide has been released in the UK in 2006, viz. SCI Publication P288, in which the BRE-Bailey method was adopted. This method allows interior secondary beams to be unprotected so that fire-protection costs can be reduced without compromising on structural safety. Many composite steel-framed buildings in the UK have since benefited from the application of the method, resulting in reduced fire protection costs for secondary steel beams. An experimental programme including 8 composite beam-slab floor system specimens had been tested under fire conditions at Nanyang Technological University from 2010-2012 to investigate the assumptions and the validity of the Bailey-BRE method. It is concluded that the Bailey-BRE method is conservative and SCI P288 can be applied in Singapore without compromising safety of steel-framed composite structures providing that detailing of structural members should be followed closely in the construction phase.